Learn QGIS : your step-by-step guide to the fundamental of QGIS 3.4 - Cutts, Andrew; Graser, Anita (Packt Publishing, 2018)
QGIS 3.4 is a user-friendly open source geographic information system (GIS) that runs on Linux, Unix, Mac OS X, and Windows. The book will take you on a journey from firing up QGIS for the first time to developing your own processing pathway. We'll look at the fundamentals of GIS: data creation, data display, creating maps and spatial analysis.